Nursing management of abortive form of herpes zoster in a patient undergoing open surgery for lumbar disc herniation (1例顿挫型带状疱疹合并腰椎开放术后患者的护理体会) - ZHANG Qian (张倩); WANG Qiujie (王秋洁) (中西医结合护理)
This paper summarizes the nursing practice of a patient with abortive form of herpes zoster after opening surgery for lumbar disc herniation. KEY issues of nursing included the management of pain, skin condition, mental states, potential complications and other aspects. Application of multi-system, multi-element, multi-approach integrated traditional Chinese and Western medicine nursing model, combined with multi-disciplinary nursing intervention, is effective to relieve the pain and negative emotion, and improve the postoperative rehabilitation. (本文总结了1例顿挫型带状疱疹合并腰椎开放术后患者的护理经验, 包括针对疼痛、皮肤、心理、潜在并发症等多个方面的管理, 运用多系统、多元素、多途径的中西医结合护理模式, 联合多学科对患者进行个体化的护理干预, 有效减轻患者疼痛, 缓解其负性情绪, 促进早期康复。)